2001
DOI: 10.1111/1467-9353.00074
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of the Educational Value of Web-Based Instructional Tools for Introductory Agricultural Economics

Abstract: A web site was designed and introduced to an introductory agricultural microeconomics course. The web site provided students with supplemental reviews, practice problems, self-tests, and a simulation exercise. A variety of quantitative assessments were conducted to determine whether the web site influenced student learning, perceptions, and motivation. Results indicate the web site provided small to modest educational benefits. I n many ways, instructors of principles of agricultural microeconomics face a uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results from studies conducted on online/web-based/distance education and virtual learning have found mixed results, ranging from positive [45][46][47] to negative [48][49][50] and even to no significantly different outcomes between the intervention and the control groups [51][52][53][54]. These results are indicative of the fact that there are several intervening variables that act as determining factors in the success of the educational technology deployed.…”
Section: Importance Of Educational Technology In Agricultural Educationmentioning
confidence: 99%
“…The results from studies conducted on online/web-based/distance education and virtual learning have found mixed results, ranging from positive [45][46][47] to negative [48][49][50] and even to no significantly different outcomes between the intervention and the control groups [51][52][53][54]. These results are indicative of the fact that there are several intervening variables that act as determining factors in the success of the educational technology deployed.…”
Section: Importance Of Educational Technology In Agricultural Educationmentioning
confidence: 99%
“…Studies testing the effectiveness of web‐enhanced classes as compared to traditional classes in economics concluded that the web enhancements result in minimal temporary improvements. Stephenson et al () tested the benefits of adding a website with reviews, practice problems, self‐tests, and a simulation exercise to their introductory agricultural economics course and found slight improvements in final course grades for two of the three classes studied. More recently, Trost and Salehi‐Isfahani () tested the effects of online homework completion on test performance and found a modest positive effect on the midterm which decays to no effect on the final exam.…”
Section: Literature Reviewmentioning
confidence: 99%